Role of Shatapushpa Churna in Prathamik Vandhyatva with Kaphaj yoni vyapad- A Review of Literature - Kumar, Suresh (International Research Journal of Ayurveda & Yoga, 2021)
GOD, the ultimate creator of universe has empowered every human being to reproduce itself and continue his existence. Childlessness may be a tragedy to the married women and can be a cause of marital upset as well as of personal unhappiness and ill health. In today’s fast world due to lack of time, mode of life and increasing mental stress, infertility is emerging as a major disorder affecting the social and psychological aspect of the life of the masses. Infertility is defined as failure to conceive within one or more years of regular unprotected coitus. According to the WHO report about 2-10 % of couples worldwide are unable to conceive primarily & about 60-80% couples in the world are infertile. Vandhyatwa has been one of the unsolved major complaints of womanhood in present era. The ancient system of Ayurvedic medicine advocated a variety of natural medication which may provide good results on this factor.